Utilizing Elbow Method for Text Clustering Optimization in Analyzing Social Media Marketing Content of Indonesian e-Commerce - Larasati, Aisyah; Maren, Raretha; Wulandari, Retno (Institute of Research and Community Outreach - Petra Christian University, 2021)
The massive increases in textual data from Twitter and text analytics simultaneously have driven organizations to obtain hidden insights to implement the proper marketing strategies for businesses. The vast information generated by Twitter enables most e-commerce businesses to utilize Twitter to implement social media marketing. One of those e-commerce businesses is Blibli Indonesia. Intense business competition has led them to perform marketing strategies to understand consumer tendencies. Focusing the marketing strategies on consumer preferences enables the increase of consumer interest in Blibli, which is in line with enhancing the opportunity to reach new consumers. This research aims to discover Twitter content based on k-means results to cluster the tweets of @bliblidotcom. The best cluster is determined with the elbow method by selecting the deepest curvature, three clusters. The result suggests that Twitter users like Park Seo Jun's content. Hence, Blibli can focus on that content as its business marketing strategy on the Twitter platform.